Effects of vitamins E and A supplementation on lipid peroxidation and concentration of some mineral in broilers reared under heat stress (32°C) - Şahin, Kazım; Şahin, Nurhan; Sari, M; Gursu, MF (Pergamon-Elsevier Science Ltd, 2002)
A study utilizing Cobb-500 male broilers was conducted to evaluate the effects of vitamin E (dl-alpha-tocopheryl-acetate), vitamin A (retinol), and their combination on their serum and liver concentrations of malondialdehyde (MDA) (an indicator of lipid peroxidation), iron (Fe) zinc (Zn), copper (Cu) and chromium (Cr) in broilers reared under heat stress (32 C). One day-old 120 broilers were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The birds were fed either a control diet or a control diet supplemented with either vitamin A (15.000 IU retinol/kg diet), vitamin E (250 mg dl-alpha-tocopheryl-acetate/kg diet), or a combination of vitamins A and E (15.000 IU retinol plus 250 mg dl-alpha-tocopheryl-acetate/kg diet). Serum MDA levels were decreased in E, A and E+A groups (1.3, 1.5, and 0.95 nmol/ml, respectively) compared with control (2.1 nmol/ml) (P < 0.05). Similarly, liver MDA levels were decreased in treatment groups (3.6, 3.9 and 2.9 nmol/g, respectively compared with control group (5.4 nmol/g) (P < 0.05). Supplemental vitamins E and A increased serum and liver concentrations of Fe, Zn and Cr (P < 0.01). Serum and liver copper concentrations, however, decreased (P < 0.05) upon vitamins E and A supplementation. In general, when a significant effect was found for a parameter, the magnitude of the responses to vitamin supplements was greatest with the combination of the vitamin A and vitamin E, rather than that of each vitamin supplement separately. Results of the present study conclude that supplementing with a combination of dietary vitamins E and A offers a good management practice for alleviating metabolic changes caused by heat stress. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: heat stress; vitamin E; vitamin A; MDA; minerals; broilers